Roger Williams' religious thought with special reference to his conception of religious liberty - Thompson, Luther Joe (The University of Edinburgh, 1952)
No doubt there are those who would question the relevance and the importance of a study- such as the one before us. The average British or American citizen if informed of the prospect of such a study would probably reply with some such comment as, "Religious liberty—well, to have it, don't wet", implying that the whole question is a completely settled issue, and a privilege mankind can assume as secure and forget. This attitude demonstrates the universal human tendency to take a heritage for granted and forget the sacrifice entailed In securing it. It also suggests an ignorance of the widespread religious tyranny in the twentieth century. Men must be forever reminded that the price of freedom is eternal vigilance and that all men do not enjoy the privileges which those who possess them take for granted Perhaps a summary of the status of religious liberty in the various political units of our world would be surprising to the average individual. Men generally were aware of the denial of the basic human freedoms in Germany under the Nazis before the last Great Mar. This tyranny was brought into sharp relief by the suffering of German Christians in concentration camps and elsewhere. The extent of liberty of belief and worship granted in Soviet Russia is a matter of debate. However, there is no question about the fact that the rapprochement of the war period between state and church has not altered the legal position of religious associations, and active religious propaganda outside the life of the church is not permitted. A brief explanation concerning the approach used in this study will be in order at this point. Chapter I endeavours to define the terms and give a brief answer to the question, "What is religious liberty?" It should be noted that because of the scope of this study and the limitation of time and space, it is Impossible to give more than the briefest outline of the history of the development of the Idea of religious liberty up to the time of Roger Williams In Chapter II. This, of course, would be a full study in Itself and the brief treatment here is presented to demonstrate that Williams' ideas were not novel and that he had drawn heavily on those who had gone before him. In much the same sense it mist be bores In mind that Chapter VI In no way makes claim to an exhaustive analysis of John Milton* s thought concerning religious and political liberty. This again would be a special study within itself—and incidentally an important one for extensive research. This chapter has been incorporated in the thesis for the purpose of bringing Williams' conception of religious and political liberty Into sharper focus by comparing and contrasting it with that of Milton.
A study of Roger Williams' religious thought with special reference to his conception of religious liberty